A nationwide 16 year analysis of trends and impact of arrythmias in transplant recipients. (25th November 2020) - Isath, A; Perembeti, S; Rao, S; Sherif, A; Correa, A; Chahal, A; Padmanabhan, D; Garg, V; Contreras, J; Mehta, D
Abstract: Background: Orthotopic heart transplantation is the most effective long-term therapy for end-stage heart disease. Denervation of transplanted heart with the loss of autonomic modulation, vasculopathy, utilization of immunosuppressant drugs, and risk of allograft rejection may result in change in the prevalence of arrhythmias in transplanted hearts. Purpose: To describe the trends, distribution and the clinical impact of arrhythmias in transplanted hearts in a large nationwide population. Methods: We queried the National Inpatient Sample with administrative codes. Cardiac transplant patients were identified using procedure ICD-9-CM codes 37.5 and 33.6. Common arrhythmias were extracted using appropriate validated ICD-9-CM codes. Statistical Analysis System (SAS) version 9.4 was used for analysis of data. Results: There was a total of 30, 020 hospitalizations of heart transplant recipients between 1999 and 2014 in the United States and 16342 (54.4%) of these had arrhythmias. The prevalence of total arrhythmias increased from 53.6% (n=1, 158) in 1999 to 67.3% (n=1, 575) in 2014. The most common arrhythmia was atrial fibrillation (26.83%) followed by ventricular tachycardia (22.86%) and the prevalence of individual arrhythmias is as shown in Figure 1. Cardiogenic shock was higher in transplanted hearts with arrhythmias when compared with patients without arrhythmias (25.96% vs 18.18%; p<0.001). Transplant recipients with arrhythmias were also associated with an increased use of mechanical circulatory device (18.22% vs 12.67%, p<0.001). The use of implantable cardiac defibrillators and permanent pacemaker was also higher in the arrhythmia group (2.19% vs 0.63% and 40.43% vs 30.24% respectively, p<0.0001). However, there was no significant difference in inpatient mortality between transplant recipients with arrhythmias and without arrhythmias (7.72% vs 6.90%, p=0.225). Further, there was no significant difference in frequency of strokes between the groups (4.98% vs 5.08%; p=0.857). The total hospital cost when adjusted for inflation was significantly higher in the arrhythmic patients, with an average cost of about $570, 415±9, 590 vs $439, 707±8362 in patients without arrhythmias (p<0.0001). The mean length of hospitalization was 44.2±0.8 days in patients with arrhythmias compared to 33.9±0.8 days in patients without arrhythmias (p<0.0001). Conclusion: A significant proportion of patients with heart transplant have cardiac arrhythmias and are associated with worse in-hospital outcomes of cardiogenic shock, increased length of stay, and cost of hospitalization. However, they are not associated with worse inpatient mortality. Funding Acknowledgement: Type of funding source: None